Contemporary Issues in Banking Regulation, Governance and Performance (Palgrave Macmillan Studies in Banking and Financial Institutions, 2018)
This book offers insights into the contemporary issues in banking with a special focus on the recent European regulatory reforms, governance and the performance of firms. Written by prestigious professors and expert academics in the field, the book also covers a diverse set of topics that have gained great importance in this sector such as firm financing, culture, risk and other challenges faced by banks. The book is of interest to scholars, students and professionals in banking.